Local and semi-local vortices in the Yang-Mills-Chern-Simons model - Buck, M. (2009)
We study BPS vortex configurations in three-dimensional U(N) Yang?Mills theories with Chern?Simons interaction coupled to scalar fields carrying flavor. We consider two kinds of configurations: local vortices (when the number of flavors Nf = N) and semi-local vortices (when Nf > N). In both cases, we carefully analyze the electric and magnetic properties and present explicit numerical solutions.